Estudio de la accesibilidad de los parques Antonio José de Sucre y Pedro Vicente Maldonado de la Ciudad de Riobamba, Provincia de Chimborazo - Inca Barahona, Cristian Andrés (2021)
Accessibility for everybody is a right, which must be based on studies and research for appropriate intervention to avoid errors that may affect citizens instead of favoring them. Throughout history, it is possible to see the changes made within the city, in terms of its growth, distribution, and population, for which a new location axis is taken into account, referring to the Sucre and Maldonado parks, as the central nucleus development of the city from its resettlement in 1779. Accessibility has undergone a total transformation due to the interventions and complications before its construction. They can be evidenced by photographic records, bibliographic data, and 3D surveys that helped to observe the problem before its transformation into a park. Although this thesis looks that key accessibility points that must be considered for future interventions to be carried out within the new nucleus proposed in this study. The related inquiries were made for the accessibility analysis for decades from creating the parks, which help a better appreciation of the experience at that time. In addition to criteria proposed as results obtained in sensory, physical, and cognitive research, understanding how people act within the city, understanding the environment surrounding it, and prioritizing accessibility at public meeting points makes easy access for all users.